2017
DOI: 10.1111/bjep.12192
|View full text |Cite
|
Sign up to set email alerts
|

An online growth mindset intervention in a sample of rural adolescent girls

Abstract: Results indicate that this intervention is a promising method to encourage growth mindsets in rural adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 37 publications
5
56
2
2
Order By: Relevance
“…e training supported the belief that abilities are malleable. is result is in line with former studies (e.g., [2,23,28]) and demonstrates once again that mindsets can be trained. In contrast to studies in which effects disappeared after a while (e.g., [4,29,30], we found the positive effect on growth mindsets to last.…”
Section: Training Effects On Beliefs and Motivationsupporting
confidence: 92%
See 2 more Smart Citations
“…e training supported the belief that abilities are malleable. is result is in line with former studies (e.g., [2,23,28]) and demonstrates once again that mindsets can be trained. In contrast to studies in which effects disappeared after a while (e.g., [4,29,30], we found the positive effect on growth mindsets to last.…”
Section: Training Effects On Beliefs and Motivationsupporting
confidence: 92%
“…For example, a training that focused on neuroscientific content supported growth mindsets, but had no impact on motivation or achievement [27]. Similarly, an online training had a stable positive effect on growth mindsets among adolescent girls, but the expected effects on motivation and academic outcomes were absent [28]. Another constraint of previous studies is that some revealed short-term, but no long-term effects.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Commonly-used individual-centered interventions range from workshops and online programs, to educational resources for teachers and parents (Bettinger et al, 2018;Burgoyne et al, 2018;Burnette et al, 2018;Cheng et al, 2017;Seaton, 2018;Singer-Freeman and Bastone, 2017). Unlike these individualcentered interventions, small group activities such as policy debate reorient participants toward assuming individual responsibility for common goal in the context of active collaboration and shared decision-making (Postmes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Growth mindset concerns the belief that an individual's basic attributes are malleable and can be cultivated through endeavors (Dweck et al, 1995;Dweck, 2015). Recently, a burgeoning body of research has demonstrated that high levels of growth mindset are positively related to optimal functions across the psychological, social, and academic domains, such as psychological well-being (Zeng et al, 2016), less mental health difficulties (Schleider et al, 2015;Schleider and Weisz, 2018;Wang et al, 2019), prosocial tendency (Han et al, 2018), self-regulation (Burnette et al, 2013;Lan et al, 2019a), learning motivation (Burnette et al, 2018), and academic achievement (Yeager et al, 2016;Wang et al, 2020). Given the salience role of growth mindset in life courses, the knowledge about the contextual and individual antecedents of growth mindset is still limited in existing research.…”
Section: Introductionmentioning
confidence: 99%